Simulasi Kebijakan Insentif Untuk Pabrik Gula dan Pekebun Tebu melalui Penetapan Imbal Jasa Pengolahan Tebu - Wahyudi, Agus; Purwono; Wulandari, Suci; Yusuf, Eddy Supriadi; Sujianto (Analisis Kebijakan Pertanian, 2023)
Currently inkind payment system in the processing of sugarcane smallholders is still dominantly implemented interm of sugar and molasses even though the system of sugarcane direct selling to sugar factory can be done. In the 2015-2019 period, there has been a significant decline in sugarcane area and national sugar production, which is thought to be partly due to the low level of incentives for planters due to the in-kind reward system for sugarcane processing. Therefore, it is necessary to to carry out incentive policy simulations for sugar factories and sugarcane smallholders by determining the fees for sugarcane processing services. This simulation aims to (1) evaluate the level of incentives obtained by sugar factory and sugarcane smallholders at the prevailing (actual) processing service rate, and (2) determine the optimal processing service rate on the target minimum incentive level obtained by sugar factory and sugarcane smallholders. By the comparative method between the actual and optimal incentive rate (with profit margin as indicator), evaluated in kind processing service rate that should be applied. The simulation results showed that the incentive obtained by sugar factory at the actual inkind processing service rate is too high, hence incentive rate obtained by sugarcane smallholders to be depressed. Consequently, they are unable to compete with other farmings. However, sugar factories can not necessarily take the benefit because most sugar factory operates below the minimum capacity and many smallholders reduce or no longer work on sugarcane, so that the sugarcane area continues to decline. To avoid the decrease in sugarcane area, it is necessary to adjust the inkind sugarcane processing service rate policy in the range of 25.35%-25.90% from 34%, and the profit margin obtained by smallholders can increase and sugarcane farming can compete with other farmings system.